Pengaruh Penambahan Kotoran Ayam terhadap Kuat Tekan Beton - Tubagus ilham pratama; Yudi Setyo Prabowo; Muhammad Oka Mahendra (Jurnal Konstruksi, 2025)
Concrete is a primary construction material widely used for its high strength and durability. However, the production of cement—the main component of concrete—contributes significantly to carbon dioxide (CO2) emissions, resulting in considerable environmental impact. Efforts to develop environmentally friendly concrete materials have been made by utilizing organic waste as an additive, one of which is chicken manure. This study aims to determine the effect of adding chicken manure on the compressive strength of normal concrete. The research was conducted experimentally in the Civil Engineering Laboratory of Universitas Serang Raya using cube specimens measuring 15 × 15 cm. The concrete mix consisted of Portland cement, fine aggregate, coarse aggregate, clean water, and dried chicken manure with addition variations of 0%, 1.5%, and 3% by weight of cement. Tests were performed on concrete specimens at the ages of 3 and 7 days using a compression testing machine. The results showed that the compressive strength values at 3 days were 11.05 MPa (0%), 12.95 MPa (1.5%), and 10.15 MPa (3%), while at 7 days they were 14.15 MPa (0%), 15.05 MPa (1.5%), and 13.2 MPa (3%). The slump value decreased as the proportion of chicken manure increased—from 110 mm in the control mix to 90 mm in the 3% mix. This indicates that higher percentages of chicken manure reduce the concrete’s workability, and compressive strength tends to decrease beyond the optimum limit. The best performance was observed with a 1.5% addition, which still met the compressive strength requirement for K-225 grade concrete, suitable for non-structural applications. Overall, incorporating chicken manure into concrete mixtures has the potential to reduce organic waste and promote the development of more environmentally friendly construction materials without significantly compromising concrete performance.